PROBLEMS AND PROSPECTS OF ELECTRONIC COMMERCE DEVELOPMENT (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes the development process of e-commerce, its advantages, problems and future prospects. E-commerce is one of the most rapidly developing sectors of the modern economy, and its development directly affects the economic stability of countries and the competitiveness of the business environment. E-commerce offers new ways of doing business and creates opportunities for small and medium-sized businesses to enter global markets. Taking this into account, the article analyzes global and national trends in e-commerce and identifies promising directions based on the experience of developed countries. Factors hindering the development of e-commerce in Uzbekistan, in particular, the underdevelopment of the Internet infrastructure, low digital literacy of small and medium-sized businesses, and lack of diversification of payment systems, are discussed in detail.